IMPACT OF FIBROMYALGIA ON DAS-28 SCORE IN RHEUMATOID ARTHRITIS: Fibromyalgia in Rhenumatiod Arthrits - Rehman, Ata Ur; Haque, afazzul-E-; Rasheed, Aflak; Wagan, Abrar Ahmed; Asghar, Ammad; Rukh, Syed Ali (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of fibromyalgia American college of rheumatology (ACR) 2010/2011 criteria) in patients with rheumatoid arthritis and its impact on disease activity score (DAS-28). Study Design: Cross-sectional study. Place and Duration of study: Department of Rheumatology and Immunology, Sheikh Zayed Hospital Lahore from Jun 2016 to Feb 2017. Patients and Methods: Total 140 diagnosed patients of rheumatoid arthritis by criteria ACR 2010 were included in this study. ACR modified 2010/2011 criterion of fibromyalgia was used to diagnose co existing fibromyalgia in these patients. Clinically disease activity status was assessed by standardized and validated DAS-28 calculator; 2ml of blood was drawn and sent to laboratory for estimation of erythrocyte sedimentation rate for all study participants. Results: The mean age, duration of disease, DAS-28 of sampled population was 49.12 ± 8.5 years, 7.36 ± 3.8 years, 4.08 ± 1.1 respectively. Out of 140 patients, 127 patients (90.7%) were females. Fibromyalgia was diagnosed in 41 patients (29.1%). The mean DAS-28 score in patients of rheumatoid arthritis with fibromyalgia was 5.39 ± .58 while for patients of without fibromyalgia it was 3.54 ± 0.69 (p-value<0.001). Conclusion: Secondary fibromyalgia is common in patients with rheumatoid arthritis and needs to be screened out in all patients diagnosed as rheumatoid arthritis and on subsequent follow up visits, coexisting fibromyalgia affects the disease activity status and this may result into inappropriate and unnecessary changes in treatment plans.